2015
DOI: 10.1186/s12978-015-0069-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of parental factors on adolescents’ transition to first sexual intercourse in Nairobi, Kenya: a longitudinal study

Abstract: BackgroundSeveral studies have demonstrated a link between young people’s sexual behavior and levels of parental monitoring, parent-child communication, and parental discipline in Western countries. However, little is known about this association in African settings, especially among young people living in high poverty settings such as urban slums. The objective of the study was to assess the influence of parental factors (monitoring, communication, and discipline) on the transition to first sexual intercourse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
59
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(74 citation statements)
references
References 40 publications
9
59
1
5
Order By: Relevance
“…The construct of ‘parent–child connection’ has also been defined as communication between parent and child21 although most studies in SSA have investigated this in relation to SRH outcomes 10. In the present review, one higher quality longitudinal study by Okigbo et al 48 found an association between parent and child ‘cross-gender’ general communication and a delay in transition to first sex at wave 2 in the TTA study48 (table 3).…”
Section: Synthesismentioning
confidence: 69%
See 3 more Smart Citations
“…The construct of ‘parent–child connection’ has also been defined as communication between parent and child21 although most studies in SSA have investigated this in relation to SRH outcomes 10. In the present review, one higher quality longitudinal study by Okigbo et al 48 found an association between parent and child ‘cross-gender’ general communication and a delay in transition to first sex at wave 2 in the TTA study48 (table 3).…”
Section: Synthesismentioning
confidence: 69%
“…Sidze et al 47 showed that parental connection was associated with safer sexual behaviour (condom use) in adolescent males 47. There was an association between parent–child ‘cross-gender’ general communication and delayed transition to sexual debut in the longitudinal study of Okigbo et al 48. However, results on the associations between parent–child communication about SRH and outcomes were inconsistent, with four studies indicating protective effects,55–58 one showing it increases risky SRH behaviour51 and two studies showing inconsistent or limited results 52 60.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Empowerment of parents regarding sexuality education is an effective intervention for promoting the adolescents' sexual health (21,24,39,40). Therefore, sensitizing parents, encouraging their interaction with the school, and empowering them in order to reduce their resistance against formal education were among the suggestions proposed by teachers and policymakers.…”
Section: Information and Motivationmentioning
confidence: 99%